Palladium Migration Through a Zirconium Carbide Coating in TRISO‐Coated Fuel Particles. Issue 4 (1st February 2016) - Geng, Xin; Yang, Fan; Liu, Han; Lu, Xiaoxiao; Xiao, Ping
Abstract : Reaction of ZrC with Pd at temperatures up to 1500°C was examined using ZrC/Pd composite, Pd/ZrC‐coated TRISO particles, and Pd/ZrC bulk diffusion couples experiments. Intermetallic phase (Pd3 Zr) and amorphous carbon at the ZrC–Pd interfaces were identified by X‐ray diffraction (XRD), Raman and scanning electron microscope (SEM). Moreover, thicknesses of Pd3 Zr layers were measured by energy‐dispersive X‐ray spectrometry (EDS). The validity of the reaction was proved by thermodynamic calculation. The reaction kinetics parameters, i.e., the activation energy (208.2–266.5 kJ/mol) and the reaction order (3.38–3.78) for Pd attacking through a ZrC coating in TRISO particles were determined based on both the DSC curves and the growth of the Pd3 Zr layer.